2008
DOI: 10.1002/nme.2511
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis for dynamic contact between high‐speed wheel and elastic beam with Coulomb friction

Abstract: SUMMARYFor numerical analysis of the dynamic contact between a high-speed wheel and an elastic beam, the equation of motion of each body is time integrated by a simple ODE solution technique and frictional contact conditions are imposed by the augmented Lagrange multiplier method using the contact errors defined in this work. For the stability of the numerical solution, the velocity and acceleration contact conditions as well as the displacement contact condition are imposed with special consideration for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…The author showed that the similar stabilizing technique using the differentiated constraints can be applied for the solution of the dynamic contact problems of rigid or elastic bodies [10][11][12][13]. For the contact problem of this work where a stiff spring is installed on the contact point, the same stabilizing technique may also be applied because the equation of motion is again a differential equation and the contact constraint is again an algebraic constraint.…”
Section: Velocity and Acceleration Contact Conditions And Contact Errorsmentioning
confidence: 97%
See 4 more Smart Citations
“…The author showed that the similar stabilizing technique using the differentiated constraints can be applied for the solution of the dynamic contact problems of rigid or elastic bodies [10][11][12][13]. For the contact problem of this work where a stiff spring is installed on the contact point, the same stabilizing technique may also be applied because the equation of motion is again a differential equation and the contact constraint is again an algebraic constraint.…”
Section: Velocity and Acceleration Contact Conditions And Contact Errorsmentioning
confidence: 97%
“…Even though the solution strategy of this work may be applied to the more complex multibody models by the author's previous work [11][12][13], for the sake of simplicity, only the two-body contact having a single contact point is considered here. Each body may be a rigid body or an elastic body, and the equation of motion of each body can be easily formulated by rigid body dynamics or finite element techniques by treating the contact force as an unknown force.…”
Section: Displacement Contact Condition and Contact Errormentioning
confidence: 99%
See 3 more Smart Citations